Interpretasi Konsep Tawassuth pada Tafsir Lathaiful Isyarat dan Tafsir Al Munir perspektif Nahdlatul Ulama - Muhammad Mansyur; Mohd Arifullah; Arfan Aziz; Nia Nursaktila (Kartika: Jurnal Studi Keislaman, 2026)
Some groups within Islam display extreme understandings that can trigger intolerant and violent actions. Although the guidelines for Muslims are based on the Quran and Hadith, in practice, there are diverse understandings and religious traditions among various groups. Therefore, this study aims to determine whether the interpretation of the Quran in these two tafsir books aligns with the principle of moderation that underpins Nahdlatul Ulama, a recognized Islamic organization that upholds a moderate stance in both religious and state life..Top of FormBottom of Form PIn this research, the author applies the interpretation method positionor comparative interpretation, namely by comparing the interpretations Lathoiful Isyarat and Interpretation Al-Munir. Library research approach (library research) The object of study is the Tafsir Lathoiful Isyarat and the Tafsir Al-Munir, while the focus of the research is Nahdlatul Ulama. Data collection was carried out using a heuristic method. The research results show that there are similarities and differences between the concept of tawassuth in the Tafsir Lathoiful Isyarat and the Tafsir Al Munir adopted by NU, namely that understanding and practicing religion must be through a path of balance and a middle ground so that religion seems friendly, gentle, and compassionate. In fact, balance is an inevitability, including in natural law. Finally, the author recommends that readers be careful in understanding anything, especially those related to tawassuth.